2016
DOI: 10.1080/14724049.2016.1145227
|View full text |Cite
|
Sign up to set email alerts
|

An innovative model of park governance: evidence from Vietnam

Abstract: Abstract:The Vietnamese Special-Use Forests policy introduced in 2006 has transformed the park and protected area governance of the country from being a state responsibility to a multicomponent system, under which power is distributed among public and private sectors. This coexisting management model is a special form of concession. This unique management model has long been applied to the management of national parks in Vietnam, but studies on the public and private sectors and/or combined management bodies c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Over the past decade, analysis of tourism policies has extensively linked to social development, such as pro-poor and community-based forms of tourism (Truong, 2013). Research on alternative forms of governance, such as community (Ngo et al, 2019), partnership (Ly and Xiao, 2016) and resource governance, has also been addressed (Nguyen et al, 2018;Khuu et al, 2021aKhuu et al, , 2021bKhuu et al, , 2022. A recent trend in policy analysis shifted focus to the governance of natural and cultural resources for sustainable development (Ly andXiao, 2016, Jeyacheya andHampton, 2020).…”
Section: Political Economics and Tourismmentioning
confidence: 99%
“…Over the past decade, analysis of tourism policies has extensively linked to social development, such as pro-poor and community-based forms of tourism (Truong, 2013). Research on alternative forms of governance, such as community (Ngo et al, 2019), partnership (Ly and Xiao, 2016) and resource governance, has also been addressed (Nguyen et al, 2018;Khuu et al, 2021aKhuu et al, , 2021bKhuu et al, , 2022. A recent trend in policy analysis shifted focus to the governance of natural and cultural resources for sustainable development (Ly andXiao, 2016, Jeyacheya andHampton, 2020).…”
Section: Political Economics and Tourismmentioning
confidence: 99%
“…Ecotourism thus provides a great alternative to massmarket tourism, especially for rural and undeveloped regions [32]. Although the purpose of ecotourism is to engage tourists in ecosystems in a low-impact, non-consumptive, and locally oriented way, in order to preserve species and habitats [32], there are significant differences between the theory and the practice of ecotourism management, especially in Southeast Asian countries [12]. The practice of ecotourism has been criticized for placing economic interests above environmental benefits, with the ultimate goal of protecting natural resources so that the tourism sector can profit from them [33][34][35].…”
Section: Ecotourismmentioning
confidence: 99%
“…Moreover, there are substantial differences between ecotourism theory and practice [12]. Despite the fact that ecotourism strikes a balance between environmental protection and socioeconomic development, case studies on this type of vacation have shown otherwise when these aspects are ignored, perverted, or manipulated [13].…”
Section: Introductionmentioning
confidence: 99%
“…시민참여를 중심으로 한 거버넌스가 점차 보편화됨에 따라 각 지자체는 시민참여를 통한 도시공원의 운영 및 관리방안을 강조하고 있다 (Kim, 2012;Ly and Xiao, 2016). 시민참여를 통 한 공원관리 시 지자체에서 제공해야 하는 인력과 비용을 절감 하려는 부분도 있지만 (Byeon et al, 2011) (Kim, 2003).…”
Section: ⅰ 서론unclassified